Peran Senam Ergonomis Untuk Kesehatan - Alfia Nurul Fatiha; Isa Ma'rufi; Dewi Rokhmah (Multidisciplinary Journal, 2021)
The higher life expectancy of a country leads to a high number of elderly people followed by high health problems in the elderly both physically and psychologically. One of the efforts to suppress all complaints to the elderly is to do ergonomic gymnastics that has been proven to provide many benefits, especially to the elderly. Ergonomic gymnastics is a gymnastics that can directly open, clean, and activate the entire body systems such as cardiovascular, urinary, reproductive systems. These movements also allow the body to be able to control, ward off some diseases and malfunctions so that the body remains healthy. Literature search from February 2019 to June 2019 using the keywords "Benefits of Ergonomic Gymnastics for The Elderly", "The Influence of Ergonomic Gymnastics for Elderly Health", "Efforts to Maintain Elderly Health", "Factors that affect Elderly Health". A total of 10 articles were selected because they meet the criteria for inclusion, namely titles and content relevant to the purpose, written in English or Indonesian, full text, published in the last 7 years. From the 10 articles selected for the review, information related to the benefits of ergonomic gymnastics for the elderly, including ergonomic gymnastics can lower anxiety levels, can improve sleep quality / insomnia, decrease chronic pain and muscle weakness, and can improve the quality of life in the elderly.